2022
DOI: 10.3390/ijerph192114378
|View full text |Cite
|
Sign up to set email alerts
|

It Is Better for Younger Workers: The Gain Cycle between Job Crafting and Work Engagement

Abstract: Job Crafting has been proposed as a new perspective, consisting in a bottom-up strategy to achieve person–job fit by emphasizing employees’ active participation and spontaneous change in job design, which is specifically adequate for older workers. Despite this fact, the cyclical influence between Work Engagement and Job Crafting over time has been less researched. We postulated that a gain cycle could be observed in the relationships between Job Crafting and its outcomes. Hence, we tested a longitudinal moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…The role of job crafting and knowledge sharing [28] . Job crafting has been proposed as a new point of view, consisting of a bottom-up approach to achieving person-job fit that places a focus on employee engagement and unplanned change in job design, which is seen as a positive indicator of proactivity [29] . Job crafting was initially thought of as the physical and mental adjustments people make to the relational or task barriers to their jobs [30] .…”
Section: Transformational Leadership Job Crafting and Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of job crafting and knowledge sharing [28] . Job crafting has been proposed as a new point of view, consisting of a bottom-up approach to achieving person-job fit that places a focus on employee engagement and unplanned change in job design, which is seen as a positive indicator of proactivity [29] . Job crafting was initially thought of as the physical and mental adjustments people make to the relational or task barriers to their jobs [30] .…”
Section: Transformational Leadership Job Crafting and Work Engagementmentioning
confidence: 99%
“…Based on job demands resources model, the dimensions of job crafting are as follows: 1) Expanding structural job resources (i.e., modifying job autonomy or variety); 2) expanding social job resources (i.e., boosting advice or support from colleagues); 3) expanding challenging job demands (i.e., enhancing for increasing demands that demonstrate difficult goals and professional development); and 4) reducing hindering job demands (i.e., deliver fewer task demands if a worker feels overburdened) [29] .…”
Section: Transformational Leadership Job Crafting and Work Engagementmentioning
confidence: 99%
“…Aynı zamanda işe adanmışlık, çalışırken yüksek düzeyde enerji ve zihinsel dayanıklılık, kişinin işine çaba harcama isteği ve zorluklar karşısında sebat etme davranışı olarak da ifade edilmektedir. Çalışanların işlerine güçlü bir şekilde dahil olarak coşku, ilham, gurur ve mücadele duygularına sahip olması işe adanmışlığın önemli göstergeleri arasındadır (Topa ve Aranda-Carmena, 2022). Çalışırken mutlu olmayı ve kuvvetli bir konsantrasyonu öngören işe adanmışlık davranışı, çalışanlar için zamanın çok hızlı geçmesini ve işten ayrılmak istememeleri sonuçlarını doğurmaktadır.…”
Section: İşe Adanmışlıkunclassified
“…Existing studies have confirmed that some factors, such as work engagement and power distance, play a mediating or moderating role in the owner’s influence on construction workers’ behaviors [ 27 , 28 ]. In construction safety management, workers’ involvement at work and the power distance between them and the owner are considered to be crucial factors affecting safety performance [ 29 , 30 ]. Nevertheless, it remains unclear whether these factors play a mediating or moderating role in the relationship between owners’ safety management behaviors and construction workers’ SCB.…”
Section: Introductionmentioning
confidence: 99%